If it's not what You are looking for type in the equation solver your own equation and let us solve it.
13-2(x+2)+5x=29
We move all terms to the left:
13-2(x+2)+5x-(29)=0
We add all the numbers together, and all the variables
5x-2(x+2)-16=0
We multiply parentheses
5x-2x-4-16=0
We add all the numbers together, and all the variables
3x-20=0
We move all terms containing x to the left, all other terms to the right
3x=20
x=20/3
x=6+2/3
| 90x+300=12300-30x | | 5c+8=-7 | | 4w-6=82 | | 18.84-11=18.13-3.9t | | B=5/4(j-72) | | -3(y+5)=y-8+2(7y+1) | | 16m-14m=18 | | 2(x+)-5=3(x+1) | | 4x-8=2x+72 | | 10x+8=2x=-16 | | -3=y+7 | | -6z-10=-5z-19 | | x²=13 | | 4x-7-3x=17 | | 10x+8=2x=16 | | 5p-3p=6+4 | | 3(h+10)=-3 | | 12x+14=−1 | | -6(-4x+2)-6x=3(x-5)-6 | | 8p-2=23 | | 7(k+8)=70 | | -4x+-8x=12 | | -6x-60+8x+20=92 | | 2a+7+6a=55 | | (5y-7)=180 | | 125m-75m+39000=40600-150m | | 25/4x=7 | | 4x+8+90=180 | | 19-5x/2=-16 | | 4k-(-7)=11 | | 6-3x/4=-5 | | 9z+13=-8 |